Instrumental isotope fractionation in multiple-collector icp-ms. Issue 8 (22nd August 2015) - Albarède, Francis; Albalat, Emmanuelle; Télouk, Philippe
<x xml:space="preserve">Abstract</x> A new law is proposed to account for the decrease of instrumental isotope fractionation in MC-ICP-MS with increasing transmission.